Budowanie planu ruchu artykulacyjnego u dzieci z zespołem Downanu ruchu artykulacyjnego u dzieci z zespołem Downa - Kuśnierz, Małgorzata; Sedivy-Mączka, Katarzyna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The authors of the article present two techniques supporting the development of articulation in children with Down syndrome: Articulation Gestures and Phoneme Manual Facilitation. Using their own clinical experience and referring to the latest neurobiological knowledge and subject literature, they justify the importance and, in some cases, the need to apply these techniques in speech therapy of children with trisomy 21. The text also presents three individual cases of children with Down syndrome of different ages who have been diagnosed with profound speech delay.